What determines market development? - Fernandez, Viviana (Journal of Financial Intermediation, 2003)
There is considerable heterogeneity in the development of derivatives markets in different countries. The question is: why? This paper addresses this question in the context of major derivatives markets in Latin America. The largest derivatives exchanges in Latin America are located in Argentina, Brazil, and Mexico. In addition, over-the-counter (OTC) markets exist in Chile and Peru. Excluding Peru, Chile's derivatives market is to date the least developed. We show that this is due to regulatory constrains and illiquidity. Domestic transactions are OTC, and consist mostly of exchange rate forwards. Recent changes in the Central Bank of Chile's exchange rate policy have not had a considerable impact on the aggregate trading volume of forwards. However, amendments made to the Law of Capital Markets in 2001 bring the possibility of having a more developed derivatives market in the future.